Insights From Mental Model Theory and Cognitive Narratology as a Tool for Content Selection in Audio Description - Vercauteren, Gert (Journal of Audiovisual Translation, 2021)
One of the main questions in audio description (AD) to which no systematic answers have been provided yet, is how to decide what information you include in your description and – if there is not enough time to describe everything – how you prioritize that information. In the present paper I want to propose an answer to this problem by asking the question: how do audiences process (filmic) stories and what information do they need to process them? The basic idea underlying this question is that people process and interpret stories by creating mental models (Johnson-Laird, 1983) of these stories. The paper explains how these models are created, what information is necessary to create them and what is optional, thus helping describers to decide what information in their description is “need-to-have” and what is “nice-to-have”. The theoretical explanation will be applied to the opening of the film Slumdog millionaire (Boyle, 2008), to illustrate how the theory works and can be used in daily practice. Lay summary Audio description (AD) for film is a service for people with sight loss that weaves a verbal description of visual elements and unclear sound effects they do not have access to, between the dialogues of the original production. Since this description cannot interfere with the dialogues, there often is very little time for AD and describers will have to decide what to include and what to leave out of their descriptions. In this article, I present a way to tackle this problem, based on the basic idea that films generally tell stories and that the audio description should allow the target audience to recreate that story in their minds. More specifically I focus on two questions, namely a) how do audiences mentally recreate stories and b) what elements do they need to do so. Insights into these two questions will show audio describers what information the target audience needs to recreate the story told in the film, and hence will help them to decide what information they really need to include in their AD. After a theoretical exploration of these two questions, the approach will be illustrated by means of a concrete example, taken from the film Slumdog millionaire (Boyle, 2008).